Research Method in the Postmodern, 1st edition - Scheurich, James (Routledge, 2020)
In recent years, research in the social sciences has been dominated by the debate on the merits of qualitative method versus quantitative methodology. Until recently, the debate appeared to have been won by those promoting the qualitative approach, but then postmodern theory appeared on the scene, challenging all our preconceptions about research method. This book goes one step further than those working at the philosophical level, showing the implications of postmodernism for practice.